The Socialization Process of EFL Teachers Working in Baja California with the National English Program for Basic Education - Márquez-Palazuelos, Ma. del Carmen Enriqueta (2018)
The present study attempts to create a better understanding of the socialization process, which teachers working in the National English Program for Basic education in Ensenada Baja California, Mexico, must experience. On one hand, findings are based on a study of the construction of teachers’ identities from a socio-pedagogical perspective and on the other hand. on a review of the context in which they are immersed.  Our purpose is not only to generalize results as to achieve a deeper understanding of the process which teachers working in the program experience, and clarify how these results influence the construction of their own identities contributing to dialog which support actions to improve their context. Descriptive data was collected through semi-structured interviews with a group of key subjects using categorization as a method of analysis to identify results. It is worth mentioning that within the findings, two classes of teachers were typified: those who command basic pedagogical knowledge because they have gone through formal training and those who have no pedagogical training, but were recruited for the job because they speak English or belong somehow to the educational system. It is also notable to mention the absence of an induction into the program upon initiating activities in an educational setting, the precarity of working conditions, the minimal support for further pedagogical training and the disesteem of communities in regards to language teachers’ social status.